1993
DOI: 10.1364/josaa.10.001509
|View full text |Cite
|
Sign up to set email alerts
|

Loci of achromatic points throughout the life span

Abstract: Mixtures of monochromatic lights that appear achromatic were measured for 50 normal, trichromatic observers ranging in age from 11 to 78 years. Stimuli were presented to one eye as a 1 degree-diameter, 1-s flash (10-s interstimulus interval) in Maxwellian view. We found the achromatic locus by varying the intensity ratio of each observer's spectral unique blue and unique yellow while maintaining constant overall retinal illuminance. Measurements were made for three levels of retinal illuminance (10, 100, 1000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 34 publications
4
84
1
1
Order By: Relevance
“…The results of this study and others 6,7,[11][12][13] are consistent with the gain change hypothesis. It is conceivable that evidence favoring the MP protection hypothesis could be obtained with our methods and a sample having different or more heterogeneous diets, but the results in this paper imply that any analysis of a protective effect of MP must take gain changes into account.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of this study and others 6,7,[11][12][13] are consistent with the gain change hypothesis. It is conceivable that evidence favoring the MP protection hypothesis could be obtained with our methods and a sample having different or more heterogeneous diets, but the results in this paper imply that any analysis of a protective effect of MP must take gain changes into account.…”
Section: Discussionsupporting
confidence: 92%
“…According to our model of compensation for age-related changes in the spectral distribution of the illuminant, 2 changes in receptor sensitivity, specified at the cornea, should be nearly parallel across cone types with increasing age, resulting in only minor shifts in unique blue, unique yellow, and the achromatic point, as has been shown empirically for subjects covering a range of approximately 60 years. 11,54 It may be noted that the loss in corneally specified sensitivity found in this study is not equal for the three types of cone mechanism, as would be expected for complete compensation. Nevertheless, the crossover points expected from the data between the S-and M-, the S-and L-, and the M-and L-cone mechanisms change from age 25 to 75 years by only Ϫ5 (482.5 to 477.5), Ϫ5 (490.5 to 485.5), and 0 (569.5) nm, respectively.…”
contrasting
confidence: 48%
See 1 more Smart Citation
“…It decreases the transmittance of visible light especially in the short wavelength range (Pokorny et al, 1987;Weale, 1988;van den Berg and Tan 1994;Xu et al, 1997). The elderly show symptoms of tritan-like defects in color discrimination (Knoblauch et al, 1987), though they have a compensation mechanism for preserving constant color appearance (Werner and Schefrin, 1993;Werner, 1996). In addition, it has been reported that age-related declines in visual performance were caused by reduction in the retinal illuminance due to changes in the ocular media and loss of efficiency at a neural level (Werner and Steele, 1988;Werner et al, 1990;Hardy et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The same results were found in this study at other light levels tested 38 and with a replication using other methods. 39 One interpretation of this finding is based on evidence that the red-green process is derived from a linear combination of signals from the three cone classes under the conditions of our measurements. The invariance across age might be expected if the receptor signals to a red-green process are reduced equally in amplitude for all three cone types, hence maintaining constant cone signal ratios across the life span.…”
Section: Hue Mechanisms and Agingmentioning
confidence: 75%